if f(x)=(1/2)x^2-x^(1/2)-3x, f(4) equals

2 Answers | Add Yours

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

We have f(x) = (1/2)x^2-x^(1/2)-3x

f(4) = (1/2)*4^2 - 4^(1/2) - 3*4

=> (1/2)*16 - 2 - 12

=> 8 - 2 - 12

=> -6

The required value is f(4) = -6

giorgiana1976's profile pic

giorgiana1976 | College Teacher | (Level 3) Valedictorian

Posted on

We'll just have to substitute x by 4 in the expression of function:

f(4) = 4^2/2 - sqrt4 - 3*4

f(4) = 16/2 - 2 - 12

f(4) = 8 - 2 - 12

f(4) = - 6

We notice that we've put x^(1/2) as sqrt x.

The value of the function is f(4) = -6.

We’ve answered 318,991 questions. We can answer yours, too.

Ask a question